2017
DOI: 10.1089/lgbt.2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Resilience Among Young Gay and Bisexual Men Living with HIV

Abstract: Purpose: HIV/AIDS disproportionately affects young gay, bisexual, and other men who have sex with men (Y-GBMSM). Resilience remains understudied among Y-GBMSM living with HIV, but represents a potentially important framework for improving HIV-related outcomes in this population. We sought to explore cognitive and behavioral dimensions of resilience and their correlates among Y-GBMSM to gain insights to inform future interventions. Methods: Our study sample consisted of 200 Y-GBMSM living with HIV enrolled in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
2
9
0
2
Order By: Relevance
“…Among our sample of BMSM in NYC, who had median resilience scores of 75 out of 100, resilience was not associated with condomless anal sex. This was unexpected given the known benefits that resilience has for sexual health behaviors among MSM, including BMSM [10, 11]. Though we also examined internalized homophobia and condom-use self-efficacy as parallel psychosocial factors, adding other variables and a larger sample size may be warranted in future studies to further examine this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among our sample of BMSM in NYC, who had median resilience scores of 75 out of 100, resilience was not associated with condomless anal sex. This was unexpected given the known benefits that resilience has for sexual health behaviors among MSM, including BMSM [10, 11]. Though we also examined internalized homophobia and condom-use self-efficacy as parallel psychosocial factors, adding other variables and a larger sample size may be warranted in future studies to further examine this question.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is the ability to recover quickly from stressful life situations; it is associated with psychological well-being and can potentially reduce HIV risk behaviors by buffering the effects of stigma and social stressors that contribute to condomless anal sex among MSM [79]. Data from mostly young black, Hispanic/Latino, and Native American MSM suggest that social supports, including family and house-ball communities (informal community networks of lesbian, gay, bisexual, transgender, and queer people), serve as sources of resilience [1011]. A study with older, HIV-infected MSM showed that resilience was positively associated with improved health-related quality of life in later years [12].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a risk or deficits-based approach to addressing the HIV epidemic focuses on what is lacking and carries the hazard of reinforcing negative stereotypes and mis-perceptions that fuel further stigma ( Herrick et al, 2013 ; Rowan et al, 2014 ). In contrast, a strengths-based approach builds on young Black GBMSM’s existing individual and community-level strengths (regardless of HIV status), recognizing the remarkable ways in which they are facing and overcoming significant barriers to both HIV prevention and care ( Aiyer, Zimmerman, Morrel-Samuels, & Reischl, 2015 ; DiFulvio, 2011 ; Herrick, Stall, Goldhammer, Egan, & Mayer, 2014 ; Hussen et al, 2017 ; Matthews et al, 2016 ). Specifically, resilience is a process through which individuals counter adversity ( Masten, Best, & Garmezy, 1990 ) and reduce or avoid negative outcomes ( Harper, Bruce, Hosek, Fernandez, & Rood, 2014 ; Luthar, Cicchetti, & Becker, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Fergus and Zimmerman, resilience is comprised of both assets (referring to internally held factors such as self-efficacy or coping skills) and resources (factors external to the individual, such as parental support or community-based organizations) that enable an individual to withstand or overcome challenges in their lives (Fergus & Zimmerman, 2005). Despite multiple, intersecting societal disadvantages, YB-GBMSM living with HIV have been observed to display both assets (e.g., strong ethnic and/or gay identity beliefs) and resources (e.g., enlisting social support, peer mentorship), and to translate these resilience factors into HIV care engagement behaviors (Harper, Bruce, Hosek, Fernandez, & Rood, 2014;Hussen et al, 2015;Hussen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%